Fostering Resilience in Experiential Learning Courses - Hackey, Robert (Experiential Learning and Teaching in Higher Education, 2023)
A focus on resilience in experiential education provides students in pre-professional programs opportunities to reflect upon their experiences as interns while also supporting their mental health and professional growth. Faculty must help students to identify strategies to manage stress and develop professional norms needed to thrive in a variety of work environments – whether in-person, hybrid, or remote. Capstone internship experiences offer an ideal setting to help students develop practical skills to support their personal and professional growth and identify their personal values and priorities. Field experience courses can foster student resilience by incorporating time for student journaling and reflection into all class meetings, encouraging students to identify strategies to forge a healthy work-life balance, and focusing on professional socialization by curating their online presence and mastering online collaborative tools such as Microsoft Teams that are vital elements of hybrid and remote work settings.